2002
DOI: 10.1175/1520-0477(2002)083<0085:trtufs>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Real-Time Ultrafinescale Forecast Support during the Special Observing Period of the MAP

Abstract: Can a real-time 3-km model of the Alps region help decipher observed complex phenomena and improve numerical weather prediction of heavy precipitation? D uring the Special Observation Period (SOP; 7 Sep-15 Nov 1999) of the Mesoscale Alpine Programme (MAP) (Bougeault et al. 2001), the Canadian Mesoscale Compressible Community Model (MC2) was run in a real-time Numerical Weather Prediction (NWP) mode. The goals of this effort were (i) to provide real-time high-resolution forecasts in support of the field phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 22 publications
0
58
0
1
Order By: Relevance
“…The operational analyses of the European Centre for Medium-Range Weather Forecasts (ECMWF) and the Vienna Enhanced Resolution Analysis (VERA) (Steinacker, et al, 2000) are used to compile a synoptic and mesoscale overview of the event. 'Quicklooks' of the operational forecast of the Canadian Mesoscale Compressible Community Model (MC2) (Benoit, et al, 2002) available from the MAP Data Centre are used for the interpretation of some observations.…”
Section: Additional Datasetsmentioning
confidence: 99%
“…The operational analyses of the European Centre for Medium-Range Weather Forecasts (ECMWF) and the Vienna Enhanced Resolution Analysis (VERA) (Steinacker, et al, 2000) are used to compile a synoptic and mesoscale overview of the event. 'Quicklooks' of the operational forecast of the Canadian Mesoscale Compressible Community Model (MC2) (Benoit, et al, 2002) available from the MAP Data Centre are used for the interpretation of some observations.…”
Section: Additional Datasetsmentioning
confidence: 99%
“…The main goal was to provide high-resolution forecasts in support of the field phase but also to gain early experience with a next-generation non-hydrostatic model. Benoit et al (2002) show that the MC2 real-time forecasts captured the timing and the structure of the precipitation events quite well but underpredicted the magnitude of the precipitation by a factor of 2. The systematic underprediction was subsequently attributed to an error in the cloud microphysical scheme, leading to an excessive residence time of cloud water in the model (Smith et al, 2003).…”
Section: Studies Covering the Entire Sopmentioning
confidence: 99%
“…Here a convection-resolving limited-area model (the MC2 in the same set-up as in Benoit et al, 2002) was used to address the role of small-scale perturbations that may grow within the model limited domain. It was found that small-scale predictability differed strongly from case to case.…”
Section: Forecast Uncertainties Predictability and Ensemble Forecastsmentioning
confidence: 99%
“…Acting like a virtual topography, this cold pool shifted the lifting of the approaching southerly flow farther south (Lin et al, 2005;Reeves and Lin, 2006), so that heavy convection was triggered offshore over the Ligurian Sea whereas only moderate stratiform precipitation was observed over the Po Valley and in the so-called Lago Maggiore Target Area (LMTA) selected for precipitation observations during MAP (Medina and Houze, 2003;Rotunno and Ferretti, 2003). It is interesting to note that the IOP 8 precipitation field was quite poorly forecast by the high-resolution operational MC2 forecasts conducted during the MAP SOP (Benoit et al, 2002) because the cold pool in the Po Valley was too weak and was eroded too rapidly (e.g. Rotunno and Ferretti, 2003).…”
Section: Introductionmentioning
confidence: 99%